Strolling in the ruins : the Caribbean's non-sovereign modern in the early twentieth century - Smith, Faith, 1964- (Duke University Press, 2023)
"In Strolling in the Ruins Faith Smith engages with a period in the history of the Anglophone Caribbean often overlooked as nondescript, quiet, and embarrassingly pro-imperial within the larger narrative of Jamaican and Trinidadian nationalism. Between the 1865 Morant Bay Rebellion and World War I, British imperialism was taken for granted among both elites and ordinary people, while nationalist discourses would not begin to shape political imagination in the West Indies for decades. Smith argues that this moment, far from being uneventful, disrupts the inevitability of nationhood in the mid-twentieth century and anticipates the Caribbean's present-day relationship to global power. Smith assembles and analyzes a diverse set of texts, from Carnival songs, poems, and novels to newspapers, photographs, and gardens to examine theoretical and literary-historiographic questions concerning time and temporality, empire and diaspora, immigration and indigeneity, gender and the politics of desire, Africa's place within Caribbeanist discourse, and the idea of the Caribbean itself. Closely examining these cultural expressions of apparent quiescence, Smith locates the quiet violence of colonial rule and the insistence of colonial subjects on making meaningful lives"--